Cobots and the benefits of their implementation in intelligent manufacturing. Issue 3 (May 2020) - Galin, Rinat; Meshcheryakov, Roman; Kamesheva, Saniya; Samoshina, Anna
Abstract: The perspective of robotics in intelligent manufacturing becomes with Industry 4.0. Increasing the profitability of production is the main goal, which also depends on the organization of safety and efficiently human-robot interaction in a shared work place. Perspective robotic solutions integrated into intelligent manufacturing makes able to contribute an increase of automation in production with safety compliance. The portability and compactness of robots allow to optimize the production process and improve efficiency. An important stage of robotics was the ability to take robots outside of barriers and place them next to humans. This robotic solutions market is growing up every year. This indicates a high demand for the introduction of robots in intelligent manufacturing. Already today we can see how the main players in automated manufacturing have taken the first steps towards Industry 4.0.